2011
DOI: 10.1080/09593330.2010.516770
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of hydroxyl radical formation and phenol decomposition using UV light emitting diodes and H2O2

Abstract: A novel process combining hydrogen peroxide (H2O2) and radiation emitted by ultraviolet light emitting diodes (UV LEDs) has been investigated. The UV LEDs were used as UV-C light sources emitting radiation in the range 257-277 nm for decomposition of the model substance phenol in water. In addition, the effect of H2O2 to phenol molar ratio and initial phenol concentration was examined. Two parameters, the decomposition efficiency of phenol and characterization of hydroxyl radical (HO*) production from H2O2 whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…(Eqs. (1-3)), which, however, can be consumed by an excess of H 2 O 2 [3,7]. These considerations are in agreement with the findings of Crittenden et al [35], who observed an attenuation of the oxidation rate in response to a high peroxide dosage in a H 2 O 2 /UV system.…”
Section: Oxidation Pre-treatmentsupporting
confidence: 78%
See 1 more Smart Citation
“…(Eqs. (1-3)), which, however, can be consumed by an excess of H 2 O 2 [3,7]. These considerations are in agreement with the findings of Crittenden et al [35], who observed an attenuation of the oxidation rate in response to a high peroxide dosage in a H 2 O 2 /UV system.…”
Section: Oxidation Pre-treatmentsupporting
confidence: 78%
“…However, the acidic pH, high salinity, lack of nutrients, low biodegradability and elevated polyphenols concentrations make it necessary to perform an adequate pre-treatment [1][2][3][4]. For the removal of phyto-toxic and low-biodegradable compounds, many advanced oxidation techniques have been proposed [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Some of these, such as ultrasonic irradiation, photo-catalysis and electrochemical processes are quite profitable because there is no need for the addition of chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in an alkaline environment, hydrogen peroxide decomposes according to a series of reactions with OH Radicals formation (reactions 5e6), which, however, can be consumed by excess H 2 O 2 (reaction 7) leading to less reactive radicals HO 2 . These species can react themselves with hydrogen peroxide restoration (reaction 8) [9,12]. The cyclical reactions are favoured by high initial peroxide doses, that, in the authors' opinion, probably reduces both the process speed and the stoichiometric ratio.…”
Section: Kinetic Analysismentioning
confidence: 95%
“…Mercury exists in nature mainly as cinnabar ores (Barnes and Seward 1997), and several of its compounds enter aquatic environment through leaching, washing of soils sediments and rocks by rain (Shrestha and Sillanpää 2008;Sillanpää 2009). In addition, artificial mode of mercury pollution includes leakage from landfills, sludge applications, and byproducts from chemical industries Vilhunen et al , 2011Rassaei et al 2009;Sillanpää and Rämö 2009). These byproducts and chemical waste are responsible for massive amounts of organic as well as inorganic forms of mercurial compounds released into environment as indicated in the report of National Research Council (2000).…”
Section: Toxicity Of Mercurymentioning
confidence: 99%